1992
DOI: 10.1073/pnas.89.11.4786
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the catalytic site of cytochrome c oxidase: specific ligands of heme a and the heme a3-CuB center.

Abstract: The three-subunit aa3-type cytochrome c oxidase (EC 1.9.3.1) of Rhodobacter sphaeroides is structurally and functionally homologous to the more complex mitochondrial oxidase. The largest subunit, subunit I, is highly conserved and predicted to contain 12 transmembrane segments that provide all the ligands for three of the four metal centers: heme a, heme a3, and CUB. A variety of spectroscopic techniques identify these ligands as histidines. We have used site-directed mutagenesis to change all the conserved hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 39 publications
7
77
0
Order By: Relevance
“…5) are found within hydrophobic regions. The conserved histidines in the transmembrane segments 11, VI, VII and X are ligands of Cu, and the haem irons Minagawa et al, 1992;Shapleigh et al, 1992a;Brown et al, 1993;Calhoun et al, 1993;Hosler et al, 1993). Two characteristic carboxylic acids are marked with arrows in the subunit 111 part (Fig.…”
Section: Soxm Purifies With Cytochrome B Soxc and A Rieske Fe-s Cementioning
confidence: 99%
“…5) are found within hydrophobic regions. The conserved histidines in the transmembrane segments 11, VI, VII and X are ligands of Cu, and the haem irons Minagawa et al, 1992;Shapleigh et al, 1992a;Brown et al, 1993;Calhoun et al, 1993;Hosler et al, 1993). Two characteristic carboxylic acids are marked with arrows in the subunit 111 part (Fig.…”
Section: Soxm Purifies With Cytochrome B Soxc and A Rieske Fe-s Cementioning
confidence: 99%
“…The subunit I is encoded by mitochondrial DNA [12], whereas the subunit IV is encoded by nuclear DNA. In addition, the two subunits interact with each other such that the subunit IV stabilizes the copper center in the subunit I [30,31,32]. A previous study reported that the COX IV formed an adduct with 4-hydroxynonenal (product of lipid peroxidation) after ethanol consumption in rats [33], suggesting a vulnerability of this subunit to ethanol stress.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The three largest subunits are encoded by mitochondrial DNA and carry the catalytic centers of the enzyme consisting of heme a, heme a, and Cu, in subunit I [5], and a bimetallic center of two Cu atoms (Cu,) in subunit I1 [6]. Some of the nuclear-coded subunits are expressed as tissue-specific isoforms.…”
Section: Identification Of Tissue-specific Isoforms For Subunits Vb Amentioning
confidence: 99%